New England Granite Works records - New England Granite Works
Correspondence and telegrams between the New England Granite Works, Hartford, Conn., and suppliers concerning the Congressional Library building. Correspondents include James G. Batterson and Bernard R. Green, superintendent, Library of Congress Building and Grounds.
Collection material in English.
Collection related to the Library of Congress Archives.
Keywords: Green, Bernard R. -- 1843-1914 -- Correspondence; Batterson, James G. -- 1823-1901 -- Correspondence; Library of Congress; Granite industry and trade -- Connecticut -- Hartford; Libraries -- Washington (D.C.) -- Design and construction